2003
DOI: 10.2737/pnw-gtr-572
|View full text |Cite
|
Sign up to set email alerts
|

Handbook to additional fungal species of special concern in the Northwest Forest Plan.

Abstract: forms; an expanded set of artificial keys to all fungal species from both handbooks; and an updated, partially illustrated glossary. The main purpose of this handbook is to help facilitate the survey, collection, and handling of potential ROD-listed fungal species by USDA Forest Service and USDI Bureau of Land Management employees. Each species is represented by a condensed description, a set of distinguishing features, and information on substrate, habitat, and seasonality. We also present a list of known sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…In our study, R. olivaceotinctus and R. arctostaphyli were the most frequent colonizers of P. ponderosa seedlings in the field and, whereas neither species of Wilcoxina significantly changed in frequency after the fire, one species of Cenococcum had a significant probability of decreasing after the fire (Figures 3 and 5a). This result has important implications for fungal conservation: R. olivaceotinctus fruiting bodies have been considered so infrequent that the species has been listed as one of special concern (Castellano et al, 2003), yet it seems to be highly abundant in soil spore banks; ready to take advantage of niche space opened by fire.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, R. olivaceotinctus and R. arctostaphyli were the most frequent colonizers of P. ponderosa seedlings in the field and, whereas neither species of Wilcoxina significantly changed in frequency after the fire, one species of Cenococcum had a significant probability of decreasing after the fire (Figures 3 and 5a). This result has important implications for fungal conservation: R. olivaceotinctus fruiting bodies have been considered so infrequent that the species has been listed as one of special concern (Castellano et al, 2003), yet it seems to be highly abundant in soil spore banks; ready to take advantage of niche space opened by fire.…”
Section: Discussionmentioning
confidence: 99%
“…The mushroom was always found in the decaying plant litter of trees like Terminalia elliptica and T. paniculata, in close proximity of Hygrocybe miniata. Castellano et al (2003) reported that cystidia are absent in this fungus, spore print white to creamy white. Kuo (2008) has mentioned that this fungus is often saprobic or mycorrhizal.…”
Section: Discussionmentioning
confidence: 81%
“…Probably the species prefers old-growth nonmanaged forests (not necessarily dark coniferous) as it develops on large logs and stumps irrelevant of tree species. It is considered as widely distributed, but rare species (CaStellano et al, 2003), listed as endangered in Finland (hYvärinen et al, 2019), and included into the Red Data Book of Yugra (vaSin & vaSina, 2013). Entoloma strigosissimum prefers rich and fertile soils and is concerned as typical species of floodplain and riparian forests (Winterhoff, 1992).…”
Section: Discussionmentioning
confidence: 99%